Factoring water harvesting into climate change adaptation: Endogenous responses by smallholder farmers in Gwanda district, Zimbabwe - Sibonokuhle Ndlovu (Cogent Social Sciences, 2020)
Climate change in the form of temperature increases and rainfall variability has intensified in the last three decades. Recent studies in Southern Africa (of which Zimbabwe is part) have indicated the extreme vulnerabilities of smallholder farmers to the impact of climate change and recommended that appropriate adaptation measures be put in place. In-field rainwater harvesting is one of the adaptation strategies that has been adopted by some smallholder farmers in drought-prone regions. The study examines the effectiveness of in-field rainwater harvesting as a climate change adaptation strategy for smallholder farmers in Gwanda district, Zimbabwe. Data was collected through semi-structured questionnaires (administered to 45 smallholder farmers) and five key informants. We find that most respondents adopted pit planting and mulching in-field rainwater harvesting techniques. A few respondents practised deep tillage, dead level contours, ephemeral stream diversion, ridges/furrows and hillside sheet runoff. In-field rainwater harvesting techniques increase the time required for crop moisture to set in resulting in improved crop yields. However, farmers are reluctant to adopt in-field rainwater harvesting techniques as they are labour intensive and some require technical expertise. We recommend the implementation of programmes that will enhance the capacity of smallholder farmers to implement various adaptation strategies.